Fractographic analysis of a dental zirconia framework: A case study on design issues - Lohbauer, Ulrich; Amberger, Gudrun; Quinn, George D.; Scherrer, Susanne S. (Journal of the Mechanical Behavior of Biomedical Materials, 2010)
Fractographic analysis of clinically failed dental ceramics can provide insights as to the failure origin and related mechanisms. One anterior 6-unit all-ceramic zirconia fixed partial denture (FPD) (Cercon®) has been clinically recovered and examined using qualitative fractography. The purpose was to identify the fracture origin and to state the reasons for failure. The recovered parts of the zirconia FPD were microscopically examined to identify classic fractographic patterns such as arrest lines, hackle, twist hackle and wake hackle. The direction of crack propagation was mapped and interpreted back to the origin of failure at the interface of the occlusal-palatal tip of the core and the veneering ceramic. An inappropriate core drop design favoring localized stress concentration combined with a pore cluster in the veneering ceramic at the core tip interface were the reasons for this premature through-the-core thickness failure. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Ceramic restoration; Dental ceramic; Failure analysis; Fixed partial denture; Fractography; Zirconia